Clients Perceptions Regarding “Health Days Celebration Activities”: A Sense Making Study by Phenomenographic Analysis Approach - Davey, Sanjeev; Davey, Anuradha; Raghav, Santosh Kumar; Singh, Jay Vir; Singh, Nirankar; Dimri, Dinesh (National Journal of Community Medicine, 2017)
Background: Many factors operate in choosing health facility services such as health days celebrations activities and this aspect has not been explored in past. Elucidation of Clients perceptions; via applying Phenomenographic approach is an issue, addressed by this study. Materials and Methods: The study was done in 2016 at health training centres of a Medical Institution in Muzaffarnagar district of India. The 10 clients were randomly selected, out of 40 -who attended each health day for 15 health days (RHTC) & 5 Health days (UHTC). The 200 clients quantitative data was supplemented by qualitative perceptions evaluation, which were further evaluated by a phenomenographic analysis on 100 clients selected randomly. Results: Mixed method research revealed that -for 5 common health days celebration activity- no significant differences in perceptions of clients at RHTC & UHTC were found (p>0.05). On further phenomenographic analysis -3 sense making concepts emerged: “Little time is available for attending health days activities”; “Feel health days celebration is an unimportant activity”; “More specific health information’s apart from health days required”. Conclusion: The health information’s in health days - needs to be specific; precise, interesting & need based for clients in order to appreciate the importance of health days utility.